Principles of assessment and outcome for occupational therapists and physiotherapists : theory, skills and application - Fawcett, Alison J. Laver, ....- (West Sussex : John Wiley & Sons, 2007)
Principles of assessment and outcome measurement for occupational therapists and physiotherapists aims to provide a coprehensive text on assessment, evaluation and outcome measurement for occupational therapy and physiotherapy students, therapists, managers and educators. The purpose of this book is to enable students, as well as qualified physiotherapists and occupational therapists, to understand the complex art and science of assessment processes, to be familiar with psychometric terms and able to identify the properties of tests in order to select and confidently implement the use of appropiriate standardised tests and outcome measures in their clinical practice research. The book explores the core principles that underpin effective and efficient therapy assessment processes across a wide range of diagnoses, age groups and practice settings. Examples of standardised tests along with case vignettes and case histories are used to help the reader apply these principles to their practice.
Includes bibliographical references and index.
Keywords: Disability evaluation; Ergotherapie; Needs Assessment; Occupational Therapy; Physical Therapy Modalities; Physical therapy